(untitled) (Eurasian Journal of Ecology, 2016)
In the article the the main results of research in forming of intergeneric crosses Tr.aestivum L x Aegilops and selected new varieties of common wheat that differ from the original forms in many biological attributes and properties. Distant hybridization provides a wide variety of promising forms for breeding.